Distance learning, face to face difficulties: perspectives in times of COVID-19 - Wenczenovicz, Thaís Janaina (2020)
Because of the pandemic, Brazilians’ schools have suspended classroom lessons in mid-March 2020 and they have started to search for alternatives to keep the process of teaching and learning during the quarantine. In other words, the technologies, apps and on-line platforms have got excellence status in the educational spaces. The study analyzes the difficulties that are imposed to accomplish the process of teaching and learning, because of the pandemic focusing on the right to education. About the methodology, the part of the time that was chosen to study was December 2019 until March 2020. This contest will be approached by a crucial and scientific exam that will show the Humans Rights to education as a speech and not just a rule. The procedure that was used of bibliography and research methodology, and also the database and statistics from INEP and speeches of 10 educators (on-line interview).